Pengelompokan Motif Tenun Ikat Sikka Berdasarkan Fungsi Pakai Kain - Epo, Amandus Lionisius; Maulina, Rini (Universitas Komputer Indonesia, 2024)
Sikka ikat weaving is one of the cultural treasures of the archipelago originating from Sikka Regency, East Nusa Tenggara. Made with skills that are passed down from generation to generation, but not much has been studied in depth in the context of visual elements and their functions in social life and their meaning content. This research becomes important in the realm of Visual Communication Design to analyze the visual elements and symbolism of weaving motifs to reveal the social functions and meanings they contain in the lives of Sikka people. The urgency of this research lies in the importance of preserving local culture as well as in-depth understanding of the values contained in the visual elements of weaving, and there are also not many studies that identify the relationship between visual elements and their functions in daily life. The purpose of this study is to analyze the visual elements of Sikka ikat weaving to determine their social function and symbolic meaning for the local community. This research uses a narrative literature review method based on Greenhalgh's theory, with data collection techniques through literature study. The research found that Sikka ikat woven fabric not only functions as a wearable object, but also as a medium of cultural communication that is full of symbolic meanings, social functions, and undergoes value transformation in the contemporary context. This research is useful for enriching visual studies, as well as supporting the preservation and development of Sikka ikat weaving as a socially relevant and creative medium of cultural communication. Keywords: Sikka Ikat weaving, motif, function of use, structural functionalism, symbolic meaning